Diagnosis of India's develpment problems and approaches to aqn alternative path (New Delhi, 1977)
The Indian Council of Social Science Research had iniated a series of discussions on Alternatives in Development in 1974 This monograph summarizes the main poliits that emerged in the course of these discussions.